1985
DOI: 10.1097/00132586-198502000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Effective Treatment of Verapamil Intoxication with 4-Aminopyridine in the Cat

Abstract: Abstract. To study the value of 4-aminopyridine as an antidote to verapamil intoxication, we subjected 12 adult cats to verapamil poisoning by administering doses of 4.0-25.0 mg/kg verapamil by intravenous infusion. Six animals were given 4-aminopyridine 2 X 0.5 mg/kg i.v. after the verapamil infusion was stopped and the other six animals (the control group) were not. Verapamil caused profound cardiovascular depression and also partial neuromuscular block, both of which were completely reversed by 4-aminopyrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…We have described a case of serious amlodipine poisoning which was successfully treated with intravenous 4‐aminopyridine. Our preference for 4‐aminopyridine is based on the lack of effectiveness with calcium salts and catecholamines (1, 2) and indeed we observed a good response upon 4‐aminopyridine administration, which corroborates earlier observations on verapamil intoxication (4–7).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We have described a case of serious amlodipine poisoning which was successfully treated with intravenous 4‐aminopyridine. Our preference for 4‐aminopyridine is based on the lack of effectiveness with calcium salts and catecholamines (1, 2) and indeed we observed a good response upon 4‐aminopyridine administration, which corroborates earlier observations on verapamil intoxication (4–7).…”
Section: Discussionsupporting
confidence: 90%
“…Therefore in calcium entry blocker overdose 4‐aminopyridine can increase the cytosolic Ca 2+ ‐concentration very efficiently independent of the calcium channels. This is demonstrated by restoration of decreased blood pressure, heart rate and atrioventricular block under conditions of verapamil intoxication in experimental animals and in humans (4–7). In the cases of verapamil intoxication described by Magdalan et al.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the effectiveness of various agents to delay cardiotoxicity during calcium channel blocker poisoning is under investigation. The use of intravenous lipid treatment, high‐dose insulin and levosimendan for delaying the cardiotoxicity from calcium channel blocker poisoning has been studied, and these agents have been observed to possess variable efficacies . Research continues to identify an effective and, if possible, specific antidote for verapamil intoxication.…”
Section: Discussionmentioning
confidence: 99%
“…Agoston et al (1984) found that 4-aminopyridine reversed verapamil toxicity in artificially ventilated cats. It acts by blocking voltage-dependent potassium channels, indirectly facilitating inward calcium movement.…”
Section: -Aminopyridinementioning
confidence: 97%